1996
DOI: 10.1126/science.271.5257.1861
|View full text |Cite
|
Sign up to set email alerts
|

Translational Control of p27 Kip1 Accumulation During the Cell Cycle

Abstract: Cell cycle phase transitions in eukaryotic cells are driven by regulation of the activity of protein kinases known as cyclin-dependent kinases (Cdks). A broad spectrum of Cdk-inhibitory activity associated with a 28-kilodalton protein (p28lck1) was induced in cells treated with the drug lovastatin or upon density-mediated growth arrest and was periodic in the cell cycle, with peak activity in G1. The p28lck1 protein was shown to be identical to p27Kip1, and the periodic or induced inhibitory activity resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
572
3
9

Year Published

1997
1997
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 817 publications
(617 citation statements)
references
References 23 publications
(7 reference statements)
31
572
3
9
Order By: Relevance
“…When this complex dissociates, p27 is freed and now available for interacting with and thereby inhibiting cdk2. In agreement with ®ndings by others (Polyak et al, 1994;Ko et al, 1993;Hengst and Reed, 1996) we have previously shown that contact-inhibition resulted in accumulation of p27 KIP1 , leading to reduced kinase activity of cdk2 and therefore to decreased phosphorylation of pRb, indicating that the observed inhibition of cdk2 in this study resulted from the action of p27 (Dietrich et al, 1997). If p16 INK4 was the critical molecule transmitting the growth-negative signals generated by cell-cell contacts, then impairing the function of p16 should lead to repression of contact-dependent inhibition of growth.…”
supporting
confidence: 93%
“…When this complex dissociates, p27 is freed and now available for interacting with and thereby inhibiting cdk2. In agreement with ®ndings by others (Polyak et al, 1994;Ko et al, 1993;Hengst and Reed, 1996) we have previously shown that contact-inhibition resulted in accumulation of p27 KIP1 , leading to reduced kinase activity of cdk2 and therefore to decreased phosphorylation of pRb, indicating that the observed inhibition of cdk2 in this study resulted from the action of p27 (Dietrich et al, 1997). If p16 INK4 was the critical molecule transmitting the growth-negative signals generated by cell-cell contacts, then impairing the function of p16 should lead to repression of contact-dependent inhibition of growth.…”
supporting
confidence: 93%
“…The abundance of p27 is thought to be regulated by translational and post-translational pathways, and less commonly at the level of transcription (Agrawal et al, 1996;Hengst and Reed, 1996;Roberts et al, 1994;Vlach et al, 1997). Our own observation suggests that the in vivo proteolysis of p27 by a CPP32-like caspase during early G 1 arrest could be an additional posttranslational regulation pathway of p27.…”
Section: Discussionmentioning
confidence: 75%
“…Recent studies are uncovering a high genetic complexity of the CDKIs and their mechanisms of regulation and inactivation. In addition to deletions, rearrangements, mutations and CpG island hypermethylation, these show additional complex features, including posttranscriptional (p21 WAF1/CIP1 ) or post-translational (p27 KIP1 , p15 INK4b ) regulation or imprinting (p27 KIP1 ) (Hatada and Mukai 1995;Pagano et al, 1995;Hengst and Reed, 1996;Li et al, 1996;Matsuoka et al, 1996;Shandu et al, 1997;Cost et al, 1997;Reynisdo ttir and Massague 1997). Regarding to untranslated regions, the transcriptional regulatory element proposed in this work for the p15 INK4b 3'-UTR is not unique in the CDKIs, since p21 WAF1/CIP1 has been shown to be not only posttranscriptionally regulated (Li et al, 1996) but also contains cis elements in its 3'-UTR involved in the regulation of transcription (Rishi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%